DAMAGE MONITORING OF CARBON FIBRE REINFORCED POLYMER UTILIZING ULTRASONIC GUIDED WAVES PHASED ARRAY METHOD - Selamat, Giovanni
Ultrasonic guided wave non-destructive testing is one of the structural health monitoring techniques utilized to analyse damage found in CFRP composites. Single actuation method pitch-catch ultrasonic guided wave testing has been successfully proven to be able to detect and locate damage. However, with the single actuation method, the detection area is limited to the placement and setup of the sensor. To improve on the single actuation method, the phased array method is developed to test the viability of signal focusing for more flexible damage detection. By modifying the single actuation method equipment setup and creating a specific program for phased array method in LabVIEW, the phased array method ultrasonic signals can be analysed. Through analysing the signals collected from the phased array method and comparing between the damaged and undamaged CFRP specimen, it can be determined whether the damage is detected in the phased array method. From the collected damaged and undamaged phased array method signals, the differences in the ultrasonic guided wave signals are very noticeable especially when focusing closer to the damage. As the damage has affected the ultrasonic wave signals, the phased array method this is a viable method for detecting damage in CFRP composite specimens. Further improvements such as, replacing the NI equipment with a higher sampling rate will improve the signal quality and provide clearer received signal with less noise. Hopefully this method will be further developed with combination of a damage location probability algorithm such as RAPID.